Peri-Ictal Changes in Depression and Anxiety in Persons With Epileptic and Non-epileptic Seizures - Hopp, Jennifer; Pahlavan, Autusa; Richert, Mary; Grimes, Kathryn; Turlington, Kate; Cassady, Maureen; Kvarta, Mark D.; Thompson, Scott M. (Frontiers in Psychiatry, 2022)
Objective. We tested the hypothesis that epileptic, but not nonepileptic, seizures would produce an improvement in comorbid depression and anxiety symptoms in the peri-ictal period, much like the antidepressant effects of electroconvulsive therapy. Methods. We examined depression and anxiety symptoms in patients admitted to an inpatient unit for continuous video electroencephalography as part of routine clinical care. Patients completed three questionnaires that included the Beck Depression Inventory-II (BDI), Montgomery Asberg Depression Rating Scale (MADRS), and Beck Anxiety Inventory (BAI) after admission, in the 24 hours following a seizure, then again 2 weeks after the last seizure. Results. In patients with epilepsy, depression and anxiety scores improved in the 24 hrs following a seizure (change in BDI = 24%; change in MADRS = 19%; change in BAI = 21%) but returned towards baseline after 2 weeks. In patients with nonepileptic seizures, depression and anxiety scores also improved in the 24 hrs following a psychogenic nonepileptic seizure (change in BDI = 17%, change in MADRS = 27%, change in BAI = 36%). There was a greater improvement in depression and anxiety scores in patients with focal-onset epilepsy (BDI = 30%, MADRS = 22%, BAI = 30%) compared to generalized seizure onset (BDI = 6%, MADRS = 12%, BAI = 8%). Conclusion. We conclude that single seizures can result in transient improvements in mood. Because seizures need not be generalized or epileptic to exert this effect, the underlying mechanisms are uncertain.